GTP regulates the microtubule nucleation activity of γ-tubulin - Gombos, Linda; Neuner, Annett; Berinski, Michael; Fava, Luca L.; Wade, Rebecca C.; Sachse, Carsten; Schiebel, Elmar (Nature cell biology, 2013)
Both subunits of αβ-tubulin that comprise the core components of microtubules bind GTP. GTP binding to α-tubulin has a structural role, whereas β-tubulin binds and hydrolyses GTP to regulate microtubule dynamics. γ-tubulin, another member of the tubulin superfamily that seeds microtubule nucleation at microtubule-organizing centres, also binds GTP; however, the importance of this association remains elusive. To address the role of GTP binding to γ-tubulin, we systematically mutagenized the GTP contact residues in the yeast γ-tubulin Tub4. Tub4GTP-mutant proteins that exhibited greatly reduced GTP affinity still assembled into the small γ-tubulin complex. However, tub4GTP mutants were no longer viable, and had defects in interaction between γ-tubulin and αβ-tubulin, decreased microtubule nucleation and defects in microtubule organization. In vitro and in vivo data show that only γ-tubulin loaded with GTP nucleates microtubules. Our results suggest that GTP recruitment to γ-tubulin enhances its interaction with αβ-tubulin similarly to GTP recruitment to β-tubulin.
Gesehen am 17.02.2020